2013
DOI: 10.1088/0004-637x/779/1/65
|View full text |Cite
|
Sign up to set email alerts
|

NARROWBAND LYMAN-CONTINUUM IMAGING OF GALAXIES ATz∼ 2.85

Abstract: We present results from a survey for z ∼ 2.85 Lyman-continuum (LyC) emission in the HS1549+1933 field and place constraints on the amount of ionizing radiation escaping from star-forming galaxies. Using a custom narrowband filter (NB3420) tuned to wavelengths just below the Lyman limit at z 2.82, we probe the LyC spectral region of 49 Lyman break galaxies (LBGs) and 91 Lyα emitters (LAEs) spectroscopically confirmed at z 2.82. Four LBGs and seven LAEs are detected in NB3420. Using V-band data probing the rest-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
144
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(160 citation statements)
references
References 67 publications
13
144
3
Order By: Relevance
“…In this case the lack of high spatial resolution data from HST for the majority of the sample prevents any detailed analysis about possible contamination by interlopers/foregrounds. These conclusions have been strengthened by recent observations by Siana et al (2015), who found no convincing detection in their deep HST imaging with WFC3-UVIS of five LyC emitters extracted from the sample of Nestor et al (2011), or by Mostardi et al (2015), who only found one robust LyC emitter after a reanalysis of a sample of 16 galaxies by Mostardi et al (2013). More interestingly, the only robust candidate LyC emitter by Mostardi et al (2015), the galaxy MD5b, has an observed ratio F UV /F LyC = 4.0 ± 2.0, equivalent to a relative escape fraction of 75%, when assuming complete transmission of the IGM.…”
Section: Comparison With Other Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In this case the lack of high spatial resolution data from HST for the majority of the sample prevents any detailed analysis about possible contamination by interlopers/foregrounds. These conclusions have been strengthened by recent observations by Siana et al (2015), who found no convincing detection in their deep HST imaging with WFC3-UVIS of five LyC emitters extracted from the sample of Nestor et al (2011), or by Mostardi et al (2015), who only found one robust LyC emitter after a reanalysis of a sample of 16 galaxies by Mostardi et al (2013). More interestingly, the only robust candidate LyC emitter by Mostardi et al (2015), the galaxy MD5b, has an observed ratio F UV /F LyC = 4.0 ± 2.0, equivalent to a relative escape fraction of 75%, when assuming complete transmission of the IGM.…”
Section: Comparison With Other Resultsmentioning
confidence: 87%
“…Iwata et al (2009), Nestor et al (2011, Mostardi et al (2013) found a significant number of ionizing sources in their surveys. In the SSA22 area, Iwata et al (2009) found evidence for f rel esc > 4% for the whole population of 73 LBGs analysed, but also provided evidence for a significant spatial offset between the ionizing and non-ionizing emission for some of them.…”
Section: Comparison With Other Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The vast majority of known high-redshift galaxies are also opaque to their own ionising radiation, as demonstrated by the success of the well-known Lyman-break selection (as emphasised recently in Cooke et al 2014). Only a few tens of objects are detected in the LyC (Iwata et al 2009;Nestor et al 2011Nestor et al , 2013Mostardi et al 2013). A LyC-leaking galaxy has then peculiar rare properties that we describe below.…”
Section: Ionising Continuum Leakage From Galaxiesmentioning
confidence: 78%